Toxicities Associated With Adoptive T-Cell Transfer for Cancer. Issue 6 (November 2015) - Yang, James C.
Abstract : Abstract: This review describes the toxicities associated with the therapeutic administration of cultured immune cells for the treatment of cancer by review of the literature. The toxicities seen are of 4 types: infection associated with preparative host immunosuppression with chemotherapy prior to cell administration, acute cytokine release by the infused cells, autoimmune complications from attacking "self-antigens" also expressed by some normal tissues, and off-target toxicities where antigens, other than the intended, are attacked. Complications from immunosuppression and cytokine release are often short-lived and currently best addressed by supportive care. Autoimmunity, either "on target, off tumor" or "off target, " is the result of the selection of imperfect target antigens. In some cases, this can be tolerated because the benefits outweigh the costs. In other cases, alternative target antigens must be found. New strategies targeting viral antigens for virally induced cancers and antigens encoded by tumor-specific mutations seem to have promise as safe and potentially effective targets for adoptive cell transfer.